(untitled) (Journal of actual problems of jurisprudence, 2018)
The article investigates the implementation of the legal policy in Republic of Kazakhstan, in particular, the ways of improving the legal system in the country. The author considers the impact of the accepted standards of the English law on the development of the national legal systems, and analyzes the main directions of the development of the civil legislation in Kazakhstan based on the implementation of certain provisions of the case law. One of the most significant matters regarding the improvement of the civil legislation is the question of strengthening the role of the judicial practice. Key words: civil relations, corporate relations, implementation, case law, English law, the legal framework integration, international standards, harmonization of legislation.